The Dynamics of Elections and Regional Election Regulations: The Urgency of Codification in Indonesia's Democratic System - Fathurokhman, Ferry; Karsa, Pipih Ludia; Gunawan, Muhammad Safaat; Rayhan, Ahmad (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2025)
This paper examines the urgency of codifying the Election Law and Regional Election Law into one integrated regulation in the Indonesian legal system. Currently, the implementation of the General Election and Regional Election are still regulated separately through Law No. 7 of 2017 and Law No. 10 of 2016, which has given rise to a number of problems, such as the lack of synchronization of implementation times, overlapping authority, and differences in implementation standards. This lack of integration also has the potential to hamper the efficiency and stability of the central and regional governments, especially ahead of the implementation of the national simultaneous Regional Election in 2024. Through a normative approach and analysis of the Constitutional Court's decisions, especially the Constitutional Court Decisions No. 55/PUU-XVII/2019 and Constitutional Court Decisions No. 85/PUU-XX/2022, this paper shows that the Regional Election should be considered as part of the Election regime. Codification of the two regulations is important to simplify the electoral system, ensure legal certainty, and strengthen the principle of people's sovereignty in the 1945 Constitution of the Republic of Indonesia. The results of this study recommend that the integration of electoral regulations through codification is a strategic step in supporting effective, efficient, and inclusive democracy in Indonesia.